PELATIHAN PEMBUATAN KONTEN PEMBELAJARAN KREATIF (CANVA) UNTUK MENINGKATKAN MUTU PEMBELAJARAN MELALUI PEMANFAATAN TEKNOLOGI PENDIDIKAN - Nurhillal, Zahroh; Ghozali, Ahmad Sulton; Gustianti, Arita; Valentin, Adelia Dwi (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
This article explains a community service activity in the form of training for creating creative learning content using Canva to improve the quality of education through the utilization of educational technology. The activity used a socialization method covering account creation, content creation, and content presentation via Canva. This was followed by a discussion method involving a Q&A session with participants who were school teachers. The activity took place at SMAN 16 in Tangerang Regency. This community service is expected to enhance teachers' abilities to create effective and creative learning materials, thereby aiding students' understanding during the teaching and learning process at school.